2008
DOI: 10.1080/02678290701751764
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and properties of non‐symmetric liquid crystal dimers containing a cholesteryl moiety

Abstract: 2008) Synthesis and properties of non-symmetric liquid crystal dimers containing a cholesteryl moiety, Liquid Crystals, 35:1, 39-44, A series of non-symmetric liquid crystal dimers having cholesteryl and 4-trans-(4-nalkylcyclohexyl)phenoxy groups were synthesized by condensation of cholesteryl vbromoalkanoates with appropriate 4-trans-(4-n-alkylcyclohexyl)phenols. The structures and thermal phase behaviour of the dimers were characterized using IR, 1 H NMR and mass spectroscopy, elemental analysis, differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…In the previous studies of unsymmetric cholesterol-based LC dimers, mostly, they had only one chiral moiety in their molecular structure, another mesogenic group such as benzoate ester, Schiff's base, azobenzene, or biphenyl did not catch a chiral tail [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Only a few researches reported the tolane mesogenic moiety was attached chiral tails such as 2S-chloro-3S-methylpentanoyloxy or 1, 3-dioxalane on the unsymmetric cholesterol-based LC dimers [26].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the previous studies of unsymmetric cholesterol-based LC dimers, mostly, they had only one chiral moiety in their molecular structure, another mesogenic group such as benzoate ester, Schiff's base, azobenzene, or biphenyl did not catch a chiral tail [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Only a few researches reported the tolane mesogenic moiety was attached chiral tails such as 2S-chloro-3S-methylpentanoyloxy or 1, 3-dioxalane on the unsymmetric cholesterol-based LC dimers [26].…”
Section: Resultsmentioning
confidence: 99%
“…Due to the great structural variety of unsymmetric compounds, the quantity of unsymmetric LC dimers is much more than that of symmetric LC dimers. In particular, unsymmetric cholesterol-based LC dimers which containing one cholesteryl moiety and another substituted aromatic mesogenic unit such as benzoate ester, Schiff's base, azobenzene, or biphenyl are especially interesting [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. This is because the chiral cholesteryl moiety entitles many unique optical properties such as selective reflection, circular dichroism, and thermo-optical effects besides the properties of conventional rigid aromatic LC dimers.…”
Section: Introductionmentioning
confidence: 99%
“…In the cases of DE-mHn and DE-mFn, on increasing the length of terminal alkyl chain (m), the melting points and clearing points decreased gradually, while cholesteric phase temperature ranges were on a narrow trend, but no obvious odd-even effect was observed. 21 However, on varying the length of methylene spacer (n), the isotropization temperatures (T i ) and the melting temperatures (T m ) exhibited an odd-even effect with a few exceptions. The same as other cholesterol-based series, 8,14 the dimesogenic compounds with an even spacer showed a higher T i and T m than those with odd spacer due to that the trans-conformation of an even spacer linked helps in attaining a better ordering.…”
Section: Characterization Of Liquid Crystal Phasementioning
confidence: 99%
“…From the practical application point of view, the single mesophase behavior and wide phase transition temperature are suitable for application to LC displays. 20,21 It is interesting that dimesogens possessing a cholesterol and an aromatic mesogenic moieties exhibit relatively simple cholesteric mesophase when two mesogen units are linked with one methylene spacer through two ester bonds by comparison with those linked with one methylene spacer through an ester bond and an ether bond, and some of them exhibit glassy liquid crystal properties. [22][23][24][25] Very recently, it has been reported that chiral dimesogens consisting of cholesterol and 4-(trans-4-n-hexylcyclohexyl)-2-substituted (H, F, Cl)-benzoic acid moieties were interconnected by 4 or 5 methylene spacers through two ester bonds.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Many liquid crystalline compounds consisting of a cholesteryl ester unit as a chiral segment joined to different mesogenic moieties such as benzoate ester, Schiff's base, azobenzene, biphenyl, tolane, etc., through flexible spacers, have been synthesised and extensively studied. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] Their liquid crystalline properties are affected by spacer length and polarity, the length of the terminal group attached to the aromatic rings, as well as the type of linking group between the spacer and mesogenic units, such as ethers and esters. They have shown interesting mesomorphic phase behaviour including SmA phases, TGB phases, blue phases and the N* mesophases.…”
Section: Introductionmentioning
confidence: 99%